The Effect of Critical Thinking Skill Categories on Students' Cognitive Learning Outcomes in Dynamic Fluids Topic - Yasmine Khabibah; Sukarmin Sukarmin (Universitas Sebelas Maret, 2025)
The objective of this study is to determine the difference in the influence of critical thinking skill categories on students' cognitive learning outcomes in dynamic fluid material. Education is a process aimed at helping students develop their potential, encompassing intellectual, moral, and life skills development. In senior high school (SHS), physics is a compulsory subject that many students find challenging. Research indicates that numerous students struggle to comprehend physics material, particularly dynamic fluids. The low learning outcomes are also influenced by the still-limited critical thinking skills among students in Indonesia. The use of a STEM approach combined with a Problem-Based Learning (PBL) model can enhance critical thinking skills and learning outcomes. This study employs a quasi-experimental design with a quantitative approach, utilizing a 2x2 factorial design. Two groups were tested: an experimental group taught using a STEM-PBL e-module and a control group using a conventional physics textbook. The population consisted of 11th-grade students at Senior High School 3 Surakarta. Data collection techniques included documentation, tests, and observation. Hypothesis testing was conducted using two-way ANOVA after meeting classical assumption tests, followed by Scheffe's post-hoc comparison. The hypothesis test results indicate a significant difference in the influence of high and low critical thinking skills on students' cognitive learning outcomes in dynamic fluid material).